Z-plasty in the treatment of unilateral cleft lip: review of its history - Sergio Carreirão; Leila Lemos Azem; Rafael Sucupira Menezes; Laila Bleibel Zraik (Revista Brasileira de Cirurgia Plástica)
The study reviews the use of Z-plasty in the cheiloplasty techniques used to treat unilateral cleft lip. It highlights the contribution of Brazilian authors, especially that of Perseu Lemos. It also reports the conduct adopted by the senior author in this type of cheiloplasty.